The recycling of e-waste in the Industrialised Global South: the case of Sao Paulo Macrometropolis. Issue 1 (2nd January 2021) - Lopes dos Santos, Kauê
ABSTRACT: E-waste production increase in the industrialised countries of the Global South follows the worldwide trend in the early 21st century. In large urban centres of these territories, e-waste disposal occurs in more significant quantities, and the need to implement a reverse logistics system within a proper regulatory and technical conditions has become a challenge. To the extent that most researches on the e-waste recycling in the developing world are dedicated to the analysis of informal stakeholders – especially in the waste collection and processing stages –, this article aims to contribute to the scientific debate by analysing the organisation of formal recyclers in Sao Paulo Macrometropolis, the most expressive consumer market of Brazil, encompassing more than 30 million inhabitants. Through a comparative case study of formal recyclers operating before the enforcement of national e-waste management regulation (2020), it was revealed some logistics limitations related to the low/irregular flow of e-waste collected, and the lack of technologies to enable the final stages of recycling. Research also points to possible synergies between the demands of these formal companies and the instruments that will be enforced by the recently approved regulation as a way to overcome these limitations in the short term partially..